The Association between School Corporal Punishment and Child Developmental Outcomes: A Meta-Analytic Review - Lotte N. Visser; Claudia E. van der Put; Mark Assink (MDPI AG, 2022)
School corporal punishment (SCP) is still widely used in many countries. Although primary studies have pointed toward detrimental effects of SCP, a quantitative review of these studies was not yet available. To gain better insight into effects of SCP, three meta-analyses were conducted on the association between SCP and children's (1) externalizing behavior, (2) internalizing behavior, and (3) school performance. These meta-analyses synthesized 21 studies (120 effect sizes; N = 67,400), 14 studies (18 effect sizes; N = 39,917), and 20 studies (47 effect sizes; N = 977,367), respectively. Studies were synthesized using a three-level approach to meta-analysis. The results revealed that SCP is positively associated with externalizing behavior (r = 0.27, p < 0.001) and internalizing behavior of children (r = 0.16, p < 0.001), and negatively with children's school performance (r = −0.11, p < 0.001). This review concludes that SCP is a risk factor for externalizing behavior, internalizing behavior, and reduced school performance of children. Other techniques than SCP should be used for class management, and we recommend psychoeducational programs for schools and the wider community in which corporal punishment is still used. These programs should convey the detrimental effects of SCP and alternative discipline techniques. More awareness of the detrimental effects of SCP is needed to make the school environment a safe place for all children across the world.